2021
DOI: 10.3390/foods10102412
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Knowledge and Practices of Pregnant Women and Postpartum Mothers in Slovenia

Abstract: Food safety during pregnancy and postpartum is important for preventing foodborne diseases, while pregnant women are considered vulnerable due to their immunomodulatory condition. The current study aimed to investigate the self-reported food safety knowledge and practices of pregnant women and postpartum mothers in Slovenia using an online questionnaire and to compare the results with nonpregnant women as a control group. The study was conducted with 426 women, of whom 145 were pregnant, 191 were not pregnant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
5
1
2
Order By: Relevance
“…In contrast to our findings, a study among women in Jordan reported that a high proportion of participants (61.6%) who use separate sets of cutting boards and knives for meat or vegetable and who wash them after each use [26]. Moreover, pregnant women in Slovenia were found to be more concerned with using separate cutting boards and knife sets as opposed to non-pregnant women [13].…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, a study among women in Jordan reported that a high proportion of participants (61.6%) who use separate sets of cutting boards and knives for meat or vegetable and who wash them after each use [26]. Moreover, pregnant women in Slovenia were found to be more concerned with using separate cutting boards and knife sets as opposed to non-pregnant women [13].…”
Section: Plos Onecontrasting
confidence: 99%
“…In the United Arab Emirates (UAE), food safety authorities and municipalities play a pivotal role in ensuring food safety in the country and promoting messages and advice to the public. In this particular group, previous international research identified gaps in knowledge and practices of basic food safety aspects in food preparation, temperature control, cross-contamination, safe food consumption, and personal hygiene [10,12,13]. Moreover, a recent study in the UAE found that non-pregnant women had an acceptable level of knowledge on food safety regarding cross-contamination and foodborne diseases but lacked detailed knowledge on risk factors for foodborne diseases and food preparation and consumption [14].…”
Section: Introductionmentioning
confidence: 99%
“…These practices align with recommendations to avoid fish high in mercury processed foods and to consume clean, fresh, and thoroughly-cooked food, as well as to wash vegetables and fruits and use clean cooking utensils (US Food and Drug Administration, 2022 ). Similarly, our findings are consistent with previous research indicating that pregnant women refrain from taking medicine without a prescription (Sychareun et al, 2022 ), reduce seafood consumption to minimize mercury exposure (Schaefer et al, 2019 ), and select safe food stalls and cooking utensils (Jevsnik et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Hasil penelitian ini sejalan dengan penelitian yang dilakukan sebelumnya dimana mayoritas ibu hamil berusia 25-36 tahun, berpendidikan tinggi, dan merupakanibu rumah tangga. [17][18][19][20][21] Pengetahuan ibu hamil tentang keamanan pangan cukup baik, mencapai hampir seluruh ibu hamil. Sejalan dengan penelitian Asiedu et al yang menunjukkan hampir seluruh ibu hamil mendapat nilai pengetahuan memuaskan tentang keamanan pangan.…”
Section: Pembahasanunclassified